Interesante momento del columnismo. - Santamaría Suárez, Luisa (Estudios sobre el Mensaje Periodístico, 2000)
Interesting moment of the column Newspaper´s columns are fluorishing this days, and by academics that there is where the best literature is found. However, the right answer or the forescat of elections results it´s not easy for columnists. As this result has to do with combination of facts, although very much studied by sociology, are still to be detected. Stuart Mill said that newspapers columns didn´t change readers mentality. Only confirm what they already have.